PENGARUH FINANCIAL DISTRESS, FINANCIAL PERFOMANCE DAN LIKUIDITAS TERHADAP STOCK RETURN - Tony Sudirgo; Yuniarwati Yuniarwati; Nurainun Bangun (Universitas Bunda Mulia, 2020)
The purpose of this research is todiscuss aboutthe effect of financial distress, financial performance, and liquidity to stock returns in manufacturing sector companies listed in Indonesia Stock Exchange from 2015 to 2017. Purposive sampling method is used in this studywhich obtained a sample of 46 companies and the data used in this study is secondary data. This research also using multiple linear regression analysis and classic assumption test using Statistical Package for Social Sciences (SPSS) 23.00. The results of this study are financial distress variable has a positive and not significant effect of the stock return, financial perfomance variable has a positive and significant effect of the stock return, and liquidity variable has a negative and not significant effect on the stock return.Keywords : stock return, return on assets, current ratio, financial distress